Community-Based Joint Business Model Design for Solutions to Implementing Technology Innovation in Small Farmers - Rustandi, Yudi; Wulandari, Restu; Savitri, Mirna (Anuário do Instituto de Geociências, 2023)
In general, small-scale farmers in rural areas often experience obstacles in implementing technological innovations offered by agricultural extension workers. Obstacles can come from within the individual breeder himself. The theory of small farmers and the theory of collective action is expected to solve the obstacles to implementing these technological innovations. This study aims to analyze and find solutions to the obstacles to implementing technological innovation at the individual level of small farmers in rural areas. Researchers took case study research with a research and development (R&D) method approach to find the construction of a joint venture model. Qualitative methods are used in Focus Group Discussion (FGD) activities. At the same time, the quantitative descriptive research method is to evaluate the results of implementing the joint venture model. The population and the evaluation research sample were members of the Ampelsari Makmur Jaya farmer group in Pasuruan Regency and the La Tulip Farmer/Women Group in Lamongan Regency. The number of respondents for the perception evaluation was 68, determined as a total sample. Data was collected through participation techniques, in-depth interviews, FGDs and surveys. The evaluation perception was analyzed using descriptive analysis and Score T. The evaluation of respondents’ perceptions resulted in the farmers accepting the establishment of community-based business units (complete feed and pastured chicken business). The solution is also considered effective in solving the obstacles to applying technological innovation by rural and small-scale farmers in Indonesia.